KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PEMBANGUNAN PADA PROYEK PEMBANGUNAN KANTOR YONZIPUR DAN JALAN DI MAKROMAN SAMARINDA - SYAIFUL BAHRI (KURVA MAHASISWA, 2018)
Occupational Safety and Health (K3) problems in Indonesia are still often neglected. This is indicated by the high number of work accident. The construction services sector is one of the most at risk of work accidents, in addition to other major sectors of agriculture, timber and mining. The number of workers in the construction sector reaches about 4.5 million people, 15% of whom only received education up to elementary level, even about 1.5% of these workers have never received any formal education.In this study, OSH planning is based on the OHSAS 18001 guidelines / standards also in accordance with the rules and technical standards related to construction in Indonesia even according to the laws and regulations issued by the government.In this research, the researcher directly conduct the implementation and implementation of Occupational Health and Safety (K3) program on labor productivity in the construction project which has been done by distributing questionnaire with the respondent is the worker who is handling the construction project, then giving the assessment about the OHS risk took place in the field, and studied how good handling action against OHS risk on project activity of yonzipur office building and road in SamarindaFrom the results of the study found that there are still many workers who do not know about K3. What is K3, how to apply K3, and so forth. This shows that the lack of attention or commitment from contractor companies to implement the OSH program well.